Heri Hidayat, Nanda, Nita, Tasya PENGEMBANGAN KREATIVITAS ANAK USIA DINI MELALUI MEDIA PEMBELAJARAN TEKNIK INFORMASI DAN KOMUNIKASI (TIK) - Heri Hidayat; Nanda Aulia; Nita Tania; Tasya Salsabila G (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2021)
Writing this journal aims to collect data on the results of research that has been done on Early Childhood Creativity Development through Information and Communication Technique (ICT) Learning Media. This journal is written in the background to find out whether through ICT learning media can help develop early childhood creativity. The data collected through the library method by collecting journals from the internet. The results showed that the development of early childhood creativity can be influenced by Information and Communication Engineering (ICT) learning media. This can be proven from the results of research from several journals that we take as data and sources.